Impact of the Increase in National Health Insurance Contributions on X-PBI Health Insurance Participants in Tanjungbalai City in 2025 - Dian Ramadha Sari; Herlina; Sri Melda (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Problems in the health sector remain a major challenge in developing countries, where the role of the government is crucial in ensuring the availability of adequate health services for the community. Improving the quality of health services is one of the important steps to overcome various health problems that occur. The X-PBI group, which is individuals who have not fully met the criteria to receive full assistance (PBI) but still need partial subsidies, often has difficulty maintaining consistency in paying contributions. This study aims to analyze the impact of the increase in National Health Insurance (JKN) contributions on X-PBI participants in Tanjungbalai City in 2025. This study used a qualitative approach with purposive sampling technique to determine informants. Data were collected through in-depth interviews, and analyzed narratively. The results showed that the Tanjungbalai City local government has taken a number of steps such as providing education about JKN procedures and facilitating access to health services. However, the policy has not been fully effective, especially in improving the quality of services received by independent participants. Limited human resources and budget are the main obstacles in its implementation. Therefore, improving primary care through strengthening facilities, medical personnel, and community-based approaches is needed.